2011
DOI: 10.1080/00071668.2011.554798
|View full text |Cite
|
Sign up to set email alerts
|

Are one early muscle pH and one early temperature measurement sufficient to detect PSE breast meat in turkeys?

Abstract: 1. Within a large flock of turkey toms (2000 BUT9 conventionally reared and slaughtered), early muscle pH measurements were randomly done to distinguish two groups of birds presenting low (fast glycolysing, GR) or normal (normal glycolysing, GN) values. 2. Subsequently, ultimate pH values and meat quality parameters were also recorded. Meat quality parameters from GR or GN samples differ more or less indicating more or less severe PSE conditions. Proteins extracted from the samples at 20 min post mortem were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This hypothesis is supported by a lower pH at 15 min postmortem in PSE turkey (Chiang et al, 2008). Eadmusik et al (2011) used 20-min postmortem pH to classify turkey breast samples as fast-glycolysing or normal-glycolysing muscle. Samples from the rapidglycolysing group had reduced solubility, which is an indicator of protein denaturation, but the ultimate pH was not significantly different from that of samples with a normal rate of glycolysis.…”
Section: Postmortem Oxidative Metabolism and Pdk4mentioning
confidence: 65%
See 1 more Smart Citation
“…This hypothesis is supported by a lower pH at 15 min postmortem in PSE turkey (Chiang et al, 2008). Eadmusik et al (2011) used 20-min postmortem pH to classify turkey breast samples as fast-glycolysing or normal-glycolysing muscle. Samples from the rapidglycolysing group had reduced solubility, which is an indicator of protein denaturation, but the ultimate pH was not significantly different from that of samples with a normal rate of glycolysis.…”
Section: Postmortem Oxidative Metabolism and Pdk4mentioning
confidence: 65%
“…However, even a small amount of PSE turkey entering the processing line can have significant negative effects on quality of the final meat products. Several investigators have attempted to define PSE meat by using objective measurements to establish a cut-off value that would separate PSE meat from normal (Barbut, 1998;Garcia et al, 2010;Eadmusik et al, 2011). One of the indicators frequently studied is carcass color because this characteristic can be measured rapidly and is amendable to use on the processing line.…”
Section: Discussionmentioning
confidence: 99%
“…SSP was extracted from the mixed meat from different chicken breast in the present study instead of only individual broiler breast. Eadmusik et al (2011) indicated that different individual turkey breast meat had different protein patterns identified by Western blotting, although the meat samples came from the same fast glycolysing group in terms of PSE syndrome development. However, the present study confirmed that the SSP composition was similar between PSE-like and normal meat samples from the perspective of meat processing.…”
Section: Ssp and Sds-pagementioning
confidence: 99%
“…The occurrence of PSE-like muscle can be up to 23.4% in China as reported by Zhu, Xu, Min, and Zhou (2012), thus resulting in more economic loss to the poultry industry (Petracci et al, 2009). Previous studies concerned the cause of the PSE occurrence and showed that a combination of high temperature and rapid pH decline in the early postmortem period induced the higher level of protein denaturation, contributing to the development of PSE-like poultry meat (Eadmusik, Molette, Fernandez, & Rémignon, 2011;Pietrzak, Greaser, & Sosnicki, 1997;Zhu, Ruusunen, Gusella, Zhou, & Puolanne, 2011;Zhu et al, 2013). Van Laack, Liu, Smith, and Loveday (2000) reported that protein solubility was performed to indicate the denatured level of protein.…”
Section: Introductionmentioning
confidence: 99%
“…representative of different steps of the glycolytic and oxidative pathways are currently used for 356 the characterization of the metabolic types of muscles in beef (Sudre et al 2005;Jurie et al 357 2006), poultry (Eadmusik et al 2011), pig (Demars et al 2007), sheep (Mascio et al 2005) 358 and camel (Abdelhadi et al 2012;Al-Owaimer et al 2014) …”
mentioning
confidence: 99%